THE ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN AN EFFORT TO IMPROVE LECTURER PERFORMANCE AT PRIVATE UNIVERSITIES IN JEMBER - Tamriatin Hidayah; Hary Sulaksono (MBA - Journal of Management and Business Aplication, 2021)
This study aims to see the influence of the variable leadership style, organizational culture, compensation on performance through the variable Organizational Citizenzhip Behavior as an Intervening variable. The research was conducted at private universities in Jember. Methods of data collection through distribution of questionnaires. The data analysis method used was SEM. The results obtained from this study are that there is a direct influence of leadership style, organizational culture, and compensation on lecturer performance. Indirect influence through the intervening variable Organizational Citizenship behavior. The implications that can be formulated in relation to the results of this study are that higher education leaders should always apply a leadership style that is able to encourage the improvement of lecturer performance. Keywords:Leadership Style, Organizational Culture, Compensation, Performance, Organizational Citizenship Behavior